Spotlight on Innovation the Future Beyond Digital-Entering a New Era of Exploration and Collaboration with Greg Satell - Satell, Greg (O'Reilly Media, Inc., 2019)
Innovation isn't just about solving existing problems faster and more efficiently; it's about discovering and solving new ones. To remain competitive, today's business leaders need to embrace not only new technologies but an entirely new mindset when it comes to innovation. Recorded on November 28, 2018. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Innovation, you'll discover what successful companies have in common and how you can follow their lead with small practical steps to transform your organization and prepare for the Next Economy.